2019
DOI: 10.1016/j.celrep.2019.10.012
|View full text |Cite|
|
Sign up to set email alerts
|

Control of Germinal Center Localization and Lineage Stability of Follicular Regulatory T Cells by the Blimp1 Transcription Factor

Abstract: Highlights d FoxP3-specific ablation of Blimp1 results in expansion of dysfunctional T FR cells d Inducible deletion of Blimp1 in T FR cells impairs T FR stability and function d Blimp1 controls CTLA4 expression, IL-23R-CD25 and CXCR5-CCR7 axes in T FR cells d Blimp1 controls appropriate homing and positioning of T FR cells into the GC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 35 publications
2
59
0
Order By: Relevance
“…These data support the third explanation that Tfr cells have additional GCB cell helper activity besides that from IL-10. We should also note that, recently, Wang et al published a study indicating that Blimp1-deficient Tfr cells are unstable and can differentiate into IL-17-producing cells that can produce IL-4 and IL-21 and promote larger GCs (56). Although this model could explain the discrepancy of larger GCs despite depleted IL-10 production from the Tfr cells, we found no evidence in our RNA-Seq data of higher Il17 in Blimp1-deficient Tfr cells (Supplemental Figure 12).…”
Section: Methodsmentioning
confidence: 87%
“…These data support the third explanation that Tfr cells have additional GCB cell helper activity besides that from IL-10. We should also note that, recently, Wang et al published a study indicating that Blimp1-deficient Tfr cells are unstable and can differentiate into IL-17-producing cells that can produce IL-4 and IL-21 and promote larger GCs (56). Although this model could explain the discrepancy of larger GCs despite depleted IL-10 production from the Tfr cells, we found no evidence in our RNA-Seq data of higher Il17 in Blimp1-deficient Tfr cells (Supplemental Figure 12).…”
Section: Methodsmentioning
confidence: 87%
“…The expression of pro-inflammatory cytokines by dysregulated Blimp1-deficient Tregs and T FR cells [ 11 ] led us to ask if Blimp1 expression in these cells may potentially regulate neuroinflammation. We then adopted the MOG 35-55 -induced EAE model [ 20 ] and mice harboring a deletion of Prdm1 in FoxP3 + T cells ( Prdm1 fl/fl FoxP3 Cre mice) [ 11 ] compared to FoxP3 YFP-Cre (WT) mice at 5–6 weeks old. Although there were insignificant differences of disease activity at the onset of EAE for both groups of mice, there were increased peak and overall disease severity for Prdm1 fl/fl FoxP3 YFP-Cre mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have emphasized this critical aspect of T FR cells, as selective deletion of T FR cells has a profound impact on immune responses, leading to the aberrant expansion of T FH cells and excessive Ab production [ 10 ]. Like other Treg subsets, T FR cells must maintain their suppressive anergic phenotype during ongoing inflammatory responses and destabilized T FR cells become ex-T FR cells that acquire effector cell activity [ 11 13 ]. We have recently shown that Blimp1, a transcription factor (TF) marking effector Tregs, is essential to maintain T FR lineage stability, appropriate positioning in the GC, and effective regulatory activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations